Establishment of human trophoblast progenitor cell lines from the chorion - Genbacev, Olga (2011)
Placental trophoblasts are key determinants of in utero development. Mouse trophoblast stem cells (mTSCs), which were first derived over a decade ago, are a powerful cell culture model for studying their self-renewal or differentiation. Our attempts to isolate an equivalent population from the trophectoderm of human blastocysts generated colonies that quickly differentiated in vitro. This finding suggested that the human placenta has another progenitor niche. Here we show that the chorion is one such site. Initially, we immunolocalized pluripotency factors and trophoblast fate determinants in the early-gestation placenta, amnion and chorion. Immunoreactive cells were numerous in the chorion. We isolated these cells and plated them in medium containing FGF and an inhibitor of activin/nodal signaling, which is required for human embryonic SC self-renewal. Colonies of polarized cells with a limited lifespan emerged. Trypsin dissociation yielded continuously self-replicating monolayers. Colonies and monolayers formed the two major human trophoblast lineages—multinucleate syncytiotrophoblasts and invasive cytotrophoblasts (CTBs). Transcriptional profiling experiments revealed the factors associated with the self-renewal or differentiation of human chorionic trophoblast progenitor cells (TBPCs). They included imprinted genes, NR2F1/2, HMGA2 and adhesion molecules that were required for TBPC differentiation. Together, the results of these experiments suggested that the chorion is one source of epithelial CTB progenitors. These findings explain why CTBs of fully formed chorionic villi have a modest mitotic index and identify the chorionic mesoderm as a niche for TBPCs that support placental growth.